The Diagnostic Stability of DSM-IV Diagnoses: An Examination of Major Depressive Disorder, Bipolar I Disorder, and Schizophrenia in Korean Patients - Kim, Won (Korean College of Neuropsychopharmacology, 2011)
OBJECTIVE: We examined the stability of diagnoses defined by the Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition (DSM-IV) (major depressive disorder [MDD], bipolar I disorder [BID], and schizophrenia [SPR]) by means of retrospective reviews of medical records. METHODS: Data from patients who met the DSM-IV criteria for the aforementioned disorders according to two psychiatrists and who were followed for at least 2 years were included in this study. We reviewed the medical records and compared the diagnosis given at the index admission with assessments made every 6 months for 2 years after discharge to determine diagnostic stability. RESULTS: A total of 138 patients with MDD, 56 patients with BID, and 107 patients with SPR who were followed for 2 years were included in the final analyses. The data showed that 84.8% of the sample retained their initial diagnosis of MDD during the first year; this figure decreased to 79.0% during the second year. During the first year, 93.5% retained their initial diagnosis of BID, and this figure decreased to 89.3% during the second year; 86.8% and 86.9% retained their diagnosis of SPR during the first and second years, respectively. CONCLUSION: This study showed the instability of three major DSM-IV diagnoses among Korean patients. Additionally, the results demonstrated that accurate diagnosis using the current diagnostic system requires longitudinal observation.